Inorganic chemistry an industrial and environmental perspective - Swaddle, T. W. 1937- (Academic Press, 1997)
This book addresses the question, What is inorganic chemistry good for? rather than the more traditional question, How can we develop a theoretical basis for inorganic chemistry from sophisticated theories of bonding? The book prepares students of science or engineering for entry into the multi-billion-dollar inorganic chemical and related industries, and for rational approaches to environmental problems such as pollution abatement, corrosion control, and water treatment. A much expanded and updated revision of the 1990 text, Applied Inorganic Chemistry (University of Calgary Press), Inorganic.
Keywords: Chemistry, Inorganic.; Environmental chemistry.; elektronické knihy; electronic books